IMPROVING QUALITY OF SERVICE IN A STERILE PROCESSING AND OPERATING ROOM SETTING - Griffiths-Turner, May; Stevenson, Ruth (Operating Room Nurses Association of Canada Journal, 2005)
Issue: To improve the quality of service provided by the Sterile Processing Department (SPD) and the Operating Room (OR) through a coordinated multi-disciplinary team approach. Project: A Steering Committee was struck consisting of members from Administration, SPD, OR and Infection Prevention and Control. The mandate was to improve the quality of service provided by the SPD and OR through evidence-based practices resulting in enhanced patient care. Infection Control was named Chair. Infection Control was viewed as having a broad perspective and a vested interest in the overall project rather than with any specific department. Meetings were held biweekly initially and then monthly once momentum was established. Specific issues were identified, an action plan was developed, timelines were established and the persons responsible for addressing specific issues were named. An evaluation process was implemented. Results: Issues addressed included: increased efficiencies when reprocessing instruments, reduced frequency of flash sterilization, removal of single use medical devices (SUMeD) from the recycle stream, review of Ethylene Oxide (ETO) sterilization, prevention of loss of surgical instruments, attained optimal inventory levels of surgical instruments, upgraded OR cleaning protocols, introduced event related sterility, developed standardized SPD staff training and demonstrated continued competency, used biological indicators to monitor sterilization of all implantables and improved quality control documentation. Solutions to these issues were developed and introduced consistent with Canadian Standards Association (CSA) Standards, Operating Room Nurses Association of Canada (ORNAC) Standards, Central Sterile Association of Ontario (CSAO) Certification practice standards and Health Canada Guidelines. Lessons Learned: This was an initiative that built strong team support through the development of working relationships, collaborative problem solving, shared leadership and increased dialogue between each department. This model of practice moved beyond the original areas to include related departments including: emergency, labour and delivery and minor procedure rooms. Achieving our mandate produced improved quality of service through best practices in the OR and SPD.